Orange essential oil in sheep diets: influence on animal performance, ruminal and cecal fermentation, and milk production and composition - Gasparina, Jennifer Mayara (2026)
The aim of this study was to evaluate the effects of orange essential oil (OEO), rich in D-limonene (93.5%), on sheep nutrition, encompassing nutrient metabolism, ruminal and cecal fermentation, methane production (in vitro and in vivo estimates), feedlot lamb performance, carcass traits, and milk production/composition in lactating ewes. In Chapter 2, the first in vivo experiment utilized 20 cannulated Dorper × Santa Inês lambs (39.6 ± 4.6 kg LW) in a randomized complete block design, with treatments: control, OEO (700, 1400, 2100 mg/kg DM), and monensin (12.5 mg/kg DM). Intake, digestibility, nitrogen balance, and ruminal fermentation were assessed. Monensin increased the molar proportions of propionate (P = 0.01), butyrate (P<0.0001), isobutyrate (P = 0.01), and isovalerate (P=0.01), reducing the acetate:propionate ratio (P<0.01), while OEO did not affect intake, ruminal fermentation parameters, nitrogen balance, or digestibility. Complementarily, an in vitro experiment tested different additives: control, OEO1000 (25 mg OEO/L), narasin (NAR13: 0.13 mg/L; NAR20: 0.48 mg/L), sodium monensin (MON25: 0.6 mg/L), essential oil blend (BEO: 86 mg Agolin Ruminant LTM/L; Feedworks), and soluble quebracho tannins (3.4 mL SilvaFeedTM/L), in TMR and Mitchell grass substrates. Gas production, DM and OM digestibility, and VFA production were evaluated. Soluble tannins significantly reduced DM digestibility (P = 0.02; 6.86%) and OM digestibility (P = 0.03; 4.1%). Mitchell grass showed lower digestibility (P<0.0001) than TMR [DM: 26.5% vs. 75.4%; OM: 28.8% vs. 73.3%]. Total gas production (P<0.0001; 38.9 vs. 123.3 mL/g DM) and methane production (P < 0.001; 2.7 vs. 9.9 mL/g DM) were also lower in Mitchell grass, with no effects of the additives on these parameters. VFA concentrations were significantly lower in Mitchell grass (P<0.0001; except for isobutyrate). Additives affected propionate (P<0.001; lower with soluble tannins), valerate (P<0.0001; higher with NAR20 and MON25), isobutyrate (P=0.04), and isovalerate (P=0.01; lower with soluble tannins), reducing the A:P ratio (P=0.01) and total VFA production (P<0.01) with soluble tannins. In Chapter 4, effects of OEO (700, 1400, 2100 mg/kg DM) and monensin (12.5 mg/kg DM) on ruminal and cecal fermentation of feedlot lambs were evaluated. In the rumen, OEO generated a quadratic effect (P=0.05) on acetate and A:P (P=0.04). Monensin increased propionate compared to the control diet (P=0.02), reducing A:P (P=0.04). In the cecum, OEO did not alter the variables, but monensin reduced acetate (P = 0.05), increased propionate (P=0.02), isobutyrate (P=0.04), and isovalerate (P=0.04), and decreased A:P (P=0.05) compared to the control. In Chapter 5, OEO (700, 1400, 2100 mg/kg DM) was evaluated compared to the control diet and monensin (12.5 mg/kg DM) on performance and carcass traits of 50 Dorper × Santa Inês lambs. OEO linearly increased DMI (g/day, %LW, %LW0.75). It did not affect ADG, but OEO700 showed a trend for higher final LW (P=0.08). In Chapter 6, lactating Dorper × Santa Inês ewes (n = 50; 70% concentrate + 30% bagasse diet) received OEO (100, 500, 1000 mg/kg DM) or monensin (25 mg/kg DM). OEO increased DMI (kg/day; P=0.004) and (g/kg LW0.75) compared to monensin. However, no differences were observed in DMI (%LW), milk production and composition, and the unsaturated FA profile. OEO1000 had a quadratic effect (P<0.0001) on milk saturated FA reduction. Lambs from ewes fed OEO showed lower ADG (P=0.01) post-weaning compared to monensin. In conclusion, OEO did not negatively affect intake, digestibility, ruminal and cecal fermentation, increased DMI in feedlot lambs and lactating ewes, and altered the milk lipid profile (reduction of saturated FA). Although further studies are needed to define optimal doses and elucidate OEO effects on ruminal fermentation and animal performance.